Exploring Kernberg's Model of Personality Functioning as a Moderator of Traits: Focus on DSM-5's Section III Alternative Model of Personality Disorder. (December 2019) - Sexton, James; Hilton, Margaret; Benson, Stephanie; Rosen, Adam
A current trend emphasizes simplified models of traits and personality functioning that would reduce individuals to as few as five potential traits and one dimension of personality functioning. However, the evidence behind those models is based on linear methods of analysis that authors from Cattell to Kernberg (2016) believe do not capture the potential moderating interaction effects of personality. Using models of traits and functioning from the DSM-5, this study demonstrates not only that traits and functioning interact, but that they do so in a rich and meaningful way that points up the dangers of collapsing these concepts. Without taking the interaction into account, satisfaction in romantic or work relationships often could not be predicted or understood. If we cannot predict satisfaction in these relationships with precision, honest confusion arises over how to guide others toward these goals. Low Detachment depends on high levels of Self-Definition, just as low Antagonism relies on high levels of Empathy to be successful. Most interestingly, negative traits and low functioning can actually lead to individual satisfaction, suggesting not only that interaction is key but that nonlinear effects may also be present.